Biological control is here to stay - Hammond, Winfred (Technical Centre for Agricultural and Rural Cooperation, 1995)
Agrochemicals are proving too expensive and difficult to obtain in many parts of Africa and, on occasions, their excessive use has proved counterproductive and even dangerous to farmers. Integrated Crop Management, using few or no agrochemicals and...